2021
DOI: 10.1177/14713012211046595
|View full text |Cite
|
Sign up to set email alerts
|

Interventions promoting family involvement with care homes following placement of a relative with dementia: A systematic review

Abstract: There is a wealth of literature investigating the role of family involvement within care homes following placement of a relative with dementia. This review summarises how family involvement is measured and aims to address two questions: (1) which interventions concerning family involvement have been evaluated? And (2) does family involvement within care homes have a positive effect on a resident’s quality of life and behavioural and psychological symptoms of dementia? After searching and screening on the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…However, we also found that residents with dementia relied on family members to monitor their conditions and advocate for them. Our finding supports a systematic review that described family involvement in residents’ care through frequent visits and associated such visits with improved health, wellbeing and quality of life for residents [ 37 ]. In another qualitative study, researchers found when staff showed intuitive knowledge they knew changes in residents and intervened even without residents’ initiation [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, we also found that residents with dementia relied on family members to monitor their conditions and advocate for them. Our finding supports a systematic review that described family involvement in residents’ care through frequent visits and associated such visits with improved health, wellbeing and quality of life for residents [ 37 ]. In another qualitative study, researchers found when staff showed intuitive knowledge they knew changes in residents and intervened even without residents’ initiation [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, we also found that residents with dementia relied on family members to monitor their conditions and advocate for them. Our nding supports a systematic review that described family involvement in residents' care through frequent visits and associated such visits with improved health, wellbeing and quality of life for residents [35] . In another qualitative study, researchers found when staff showed intuitive knowledge they knew changes in residents and intervened even without residents' initiation [21] .…”
Section: Supporting Residents' Competence In Mastering Their Own Caresupporting
confidence: 85%
“…This systematic review and the second paper in this series (Interventions promoting family involvement with care homes following placement of a relative living with dementia: A systematic review. (Hayward et al, 2021) provide a comprehensive view of FI, including a proposed new definition, the nature of FI and process involved, how FI relates to PCC and FCC principles, measures of FI, the impact of FI on residents' wellbeing and how FI is being promoted in care homes. Together, the papers support researchers and care home providers to make informed decisions in the dementia field.…”
Section: Implications For Clinical Practicementioning
confidence: 99%